Effectivenes of Aerobic and Yoga Exercise to Increase Cardiorespiration Stamina in Carier Women - Esti Yunitasari; Nuzul Qur'aniati; Ida Arunia (Jurnal Ners, 2009)
Introduction : Cardiorespiratory endurance is one of the components of fitness. Cardiorespiratory endurance is considered to have relation with health because the low grade of fitness connected to high risk of immature death especially cardiovascular disease. Sport such as aerobic exercise and yoga exercise is one of efforts to increase cardiorespiratory endurance. This study was aimed to analyze the effectiveness aerobic exercise and yoga exercise to increase of cardiorespiratory endurance in female employee.Method : The design of the study was Quasy Experimental by using non-probability sampling (purposive sampling). Total sample of this study were 21 respondents. Seven respondents as treatment aerobic exerciser, 7 respondents as treatment yoga exerciser and 7 respondents as control group. The independent variables were aerobic exercise and yoga exercise. The dependent variables were the increase cardiorespiratory endurance. The data were collected and analyzed by using paired t test and anova with significance level a < 0,05.Result : The result showed that there were no differences effectiveness aerobic exercise and yoga exercise to increase cardiorespiratory endurance for female employee which were indicated by pulse (p=0,388), blood pressure systole (p= 0,520), blood pressure diastole (p=0,131) and respiration (p=0,432).Conclusion :  It can be concluded that both of gymnastic aerobic and yoga effective on increasing immunity of cardiovascular for the female. Discussion : Female employee can consider aerobic and yoga as an effort to increase cardiorespiratory endurance.